Flagellin Glycosylation in Pseudomonas aeruginosa PAK Requires the O-antigen Biosynthesis Enzyme WbpO - Miller, Wayne L. (2007)
Pseudomonas aeruginosa PAK (serotype O6) produces a single polar, glycosylated flagellum composed of a-type flagellin. To determine whether or not flagellin glycosylation in this serotype requires O-antigen genes, flagellin was isolated from the wild type, three O-antigen-deficient mutants wbpL, wbpO, and wbpP, and a wbpO mutant complemented with a plasmid containing a wild-type copy of wbpO. Flagellin from the wbpO mutant was smaller (42 kDa) than that of the wild type (45 kDa), or other mutants strains, and exhibited an altered isoelectric point (pI 4.8) when compared with PAK flagellin (pI 4.6). These differences were because of the truncation of the glycan moiety in the wbpO-flagellin. Thus, flagellin glycosylation in P. aeruginosa PAK apparently requires a functional WbpO but not WbpP. Because WbpP was previously proposed to catalyze a metabolic step in the biosynthesis of B-band O-antigen that precedes the action of WbpO, these results prompted us to reevaluate the two-step pathway catalyzed by WbpO and WbpP. Results from WbpO-WbpP-coupled enzymatic assays showed that either WbpO or WbpP is capable of initiating the two-step pathway; however, the kinetic parameters favored the WbpO reaction to occur first, converting UDP-N-acetyl-D-glucosamine to UDP-N-acetyl-D-glucuronic acid prior to the conversion to UDP-N-acetyl-D-galacturonic acid by WbpP. This is the first report to show that a C4 epimerase could utilize UDP-N-acetylhexuronic acid as a substrate.